Assessment of serum sodium levels in patients of lower respiratory tract infections (LRTI) in children at tertiary care center - Shruti Jain; Vinod Kumar; Sangeeta Kapoor; Santosh Bhalke; Shivanshu Gupta (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Lower respiratory tract infection is an infection beneath the larynx which includes: Pneumonia, Wheeze associated Lower respiratory tract infection, Bronchiolitis and Empyema. The aim of this study was to find out the association among hyponatremia and LRTI in tertiary care center.Materials and Methods: The sample size was calculated to be a minimum of 50 subjects. Based on clinical signs and symptoms (as defined by WHO) and infiltrates present on chest X-ray diagnosis of LRTI such as Pneumonia, Bronchiolitis was made. Then patients were subjected to routine investigations such as: Complete blood count, Serum electrolyte (serum sodium) at the time of admission, on day 2 and day 3 by Ion selective electrodes.Results: Mild hyponatremia was found among 11 patients (16.92%), moderate among 9 (13.85%) and severe among 2 (3.08%) patients. Hyponatremia was found to be more common among 1 to 5 years age group as compared to ≥ 2months to 12 months and > 5 to 12 years age groups.Conclusion: Hyponatremia is a significantly common association among hospitalized children with lower respiratory tract infections and it is mainly due to syndrome of inappropriate antidiuretic hormone secretion (SIADH).